Pengaruh Kualitas, Kemampuan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Di PT Melia Cakrawala Indonesia - Dina Novira; Yamasitha; Selvi Yona Sari (CV. ITTC INDONESIA, 2025)
This study aims to determine how the Effect of Quality and Work Ability on Employee Performance Through Job Satisfaction as an Intervening Variable at PT Melia Cakrawala Indonesia. The sample in the study was 45 respondents. The results of this study indicate that quality has no effect and is insignificant to job satisfaction, work ability has a significant effect on job satisfaction, quality has a significant effect on employee performance, work ability has a significant effect on employee performance, job satisfaction has a significant effect on performance, quality has no effect and is insignificant to employee performance through job satisfaction, work ability has a significant effect on employee performance through job satisfaction.